Enhancing Efficiency and Reducing Stress in Pre-Medical Students through Hybrid Competency-Based Learning - Ekvitayavetchanukul, Pongkit; Ekvitayavetchanukul , Patraporn (International Journal of Applied Educational Research (IJAER), 2024)
Contemporary high school education presents various learning modalities, encompassing traditional in-class learning, distance learning incorporating online platforms, and e-learning. Amid the prevalent challenges posed by the COVID-19 pandemic, Hybrid Competency-Based Learning (HCBL) has emerged as a popular and effective educational approach. HCBL involves a combination of online e-learning (Ananga & Biney, 2017) and in-class instruction, augmented by hands-on activities in the medical field. This research aims to demonstrate the efficacy of HCBL in fostering successful learning outcomes and mitigating stress levels among students pursuing higher education in the medical domain. The findings reveal that HCBL not only enhances learning efficiency but also contributes significantly to stress reduction, particularly in the transition to university-level studies.